New alkaloids from Phoebe scortechinii - Awang, Khalijah; Mukhtar, Mat Ropi; Mustafa, Mohd Rais; Litaudon, M.; Shaari, K.; Mohamad, K.; Hadi, A.H.A. (Taylor & Francis, 2007)
The leaves of the Phoebe scortechinii (Gamb.) Kochummen Comb. Nov. (Lauraceae), afforded one new proaporphine-tryptamine dimer; ()-phoebescortechiniine (1), along with two known ones; phoebegrandine A and phoebegrandine B. The proaporphine, tetrahydropronuciferine(2), was isolated for the first time as a natural product. The alkaloids were elucidated primarily by means of high field NMR and HRMS